Resilience in hospitality and tourism: issues, synthesis and agenda (Publication with Expression of Concern. See OCT, 2025) - Hall, C. Michael; Safonov, Alexander; Koupaei, Sarah Naderi (Emerald Group Publishing Ltd, 2023)
Purpose This paper aims to identify research approaches and issues in relation to the main paradigms of resilience: engineering resilience, ecological resilience and socio-ecological resilience. This paper provides a synthesis of the core elements of each resilience approach and their implications. Design/methodology/approach A critical thematic review was undertaken of the hospitality and tourism resilience literature. Findings Resilience is a contested boundary object with different understandings according to conceptual and disciplinary position. The dominant approach in hospitality and tourism studies is primarily informed by engineering resilience with the focus at the organizational level. The ontological and epistemological understanding of resilience and change concepts appears limited leading to a lack of appreciation of the multi-scaled nature of resilience and the importance of slow change. Research/limitations/implications The research has important implications for understanding the key elements of different approaches to resilience. Practical implications The research synthesis may help improve resilience strategy and policymaking, including indicator selection. Social implications The research notes the relationship of resilience to sustainability, the potential for learning and decision-making practices. Originality/value In addition to thematic analysis, a model of the multi-scaled nature of resilience is provided and the key elements of the three main approaches with implications for theory and practice.
Keywords: Business environment; Change; Complexity; Managerial uncertainty; Policy environment; Tourism system